2016
DOI: 10.1016/j.fertnstert.2016.07.1011
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst formation rate can be predicted by an automatic system independently of the number of oocytes retrieved and the morphology of the embryos on day 3

Abstract: OBJECTIVE: To correlate the different categories provided by an automatic diagnostic test (Eeva) with the blastocyst formation rate and to assess possible confounding factors associated to such correlation. DESIGN: Observational, retrospective, multi-center cohort study. MATERIALS AND METHODS: A total of 3002 embryos from patients undergoing egg donation cycles were imaged with the Eeva System. The Eeva system provides dark-field image and automatic cell-division tracking without the intervention of the embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since the early days of blastocyst culture, many previous studies have investigated the association between conventional morphology assessment and the rates of blastocyst formation [ 28 30 ]. However, only a few studies quantitatively evaluated the predictive power [ 16 , 18 ]. Basile et al evaluated the predictive power for blastocyst formation of morphological criteria defined by the Spanish Association of Embryologists (ASEBIR), showing an AUC of 0.717 (CI95%: 0.703–0.732), which is close to the AUC derived from Eeva time lapse system in the same population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early days of blastocyst culture, many previous studies have investigated the association between conventional morphology assessment and the rates of blastocyst formation [ 28 30 ]. However, only a few studies quantitatively evaluated the predictive power [ 16 , 18 ]. Basile et al evaluated the predictive power for blastocyst formation of morphological criteria defined by the Spanish Association of Embryologists (ASEBIR), showing an AUC of 0.717 (CI95%: 0.703–0.732), which is close to the AUC derived from Eeva time lapse system in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor-looking day 3 embryos rejected by conventional embryo morphological assessment may also have a chance to develop into blastocysts and it is believed that the associations between morphology and blastocyst formation do not necessarily correlate with blastocyst viability. Nevertheless, data from studies predicting blastocyst formation using conventional morphological assessment and time-lapse microscopy in the same population [ 16 , 18 ], showed that AUCs of conventional embryo morphological assessment for blastocyst formation were close to that of time-lapse microscopy. Especially, in the work of Petersen et al, which compared six time-lapse algorithms in the same study, only two algorithm surpassed an algorithm based on conventional Alpha/ESHRE consensus assessment in terms of predictive power [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early days of blastocyst culture, many previous studies have investigated the association between conventional morphology assessment and the rates of blastocyst formation [28][29][30]. However, only a few studies quantitatively evaluated the predictive power [16,18]. Basile et al evaluated the predictive power for blastocyst formation of morphological criteria de ned by the Spanish Association of Embryologists (ASEBIR), showing an AUC of 0.717 (CI95%: 0.703-0.732), which is close to the AUC derived from Eeva time lapse system in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years,'OMICS' technologies [6], and algorithms created through the use of time-lapse microscopy [7] were used to predict the destiny of day 3 embryos during in vitro culture. While 'OMICS' technologies, such as proteomics and metabolomics for non-invasive embryo developmental capacity assessment, are yet to be recommended for routine use [1], time-lapse microscopy has been introduced as a routine clinical practice and showed a capacity to predict the blastocyst formation with AUCs ranging from 0.6-0.8 across different studies [8][9][10][11][12][13][14][15][16][17][18][19]. Unfortunately, novel technologies inevitably require additional cost or equipment and the expense of technologies may limit their widespread use.…”
Section: Introductionmentioning
confidence: 99%